Lessons from an online vaccine communication project. Issue 44 (22nd October 2018) - Finnegan, Gary; Holt, Daphne; English, Peter M.; Glismann, Steffen; Thomson, Angus; Salisbury, David M.; Bogaerts, Hugues; Bonanni, Paolo
Abstract: Most members of the general public use the internet to research health topics. However, the quality of vaccine-related material available online is mixed and internet search engines often bring web users to low-quality anti-vaccine websites. We present a case study of a pro-vaccine information hub launched in 2011. Vaccines Today provides high-quality information about vaccines and diseases, expert interviews, answers to frequently asked questions, parent/patient stories and videos/infographics. Twitter, Facebook, YouTube and Instagram are used to share this content and to engage with various online audiences. This Commentary outlines what works in online communication about vaccines and offers proposals for improving the impact of online vaccine advocacy. The value of networking to boost visibility and search engine ranking is emphasised. Furthermore, we present the case for the sharing and application of best practice in online communication.